2008
DOI: 10.1016/j.actbio.2007.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extracellular matrix analogues on primary human fibroblast behavior

Abstract: In vitro cell culture is a vital research tool for cell biology, pharmacology, toxicology, protein production, systems biology and drug discovery. Traditional culturing methods on plastic surfaces do not accurately represent the in vivo environment, and a paradigm shift from two-dimensional to three-dimensional (3-D) experimental techniques is underway. To enable this change, a variety of natural, synthetic and semi-synthetic extracellular matrix (ECM) equivalents have been developed to provide an appropriate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 45 publications
3
37
0
Order By: Relevance
“…Previous studies have shown Carbylan-GSX is biocompatible and nontoxic to fibroblasts, and it enhances overall healing and tissue regeneration in in vitro 2D environment and in in vivo animal models. [14][15][16][17] HA is a ubiquitous connective tissue glycosaminoglycan that is a vital element of the ECM, providing tissues with an optimal environment for cell attachment, 14,18 migration, and growth. 15 In addition, HA is an important mediator of the inflammatory cascade, not only recruiting immune cells to the site of wounded tissue, but contributing to granulation tissue formation, 15 amplifying the normal wound-healing response, and promoting tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown Carbylan-GSX is biocompatible and nontoxic to fibroblasts, and it enhances overall healing and tissue regeneration in in vitro 2D environment and in in vivo animal models. [14][15][16][17] HA is a ubiquitous connective tissue glycosaminoglycan that is a vital element of the ECM, providing tissues with an optimal environment for cell attachment, 14,18 migration, and growth. 15 In addition, HA is an important mediator of the inflammatory cascade, not only recruiting immune cells to the site of wounded tissue, but contributing to granulation tissue formation, 15 amplifying the normal wound-healing response, and promoting tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…16 Specific compositions of an HA-based semisynthetic mimic of the native ECM have been optimized for human fibroblasts. 17 To further build on our previous research demonstrating the effectiveness of HA hydrogels in a prophylactic injury model of the vocal fold lamina propria, we developed a rabbit vocal fold scar model to assess three approaches for tissue regeneration. The purpose of this study was to determine if the biomechanical and biological properties of vocal fold lamina propria scar could be improved with injection of (i) autologous fibroblasts, (ii) a semisynthetic ECM (sECM), or (iii) autologous fibroblasts encapsulated into the sECM when compared to saline-treated controls.…”
mentioning
confidence: 99%
“…7,8 This versatile sECM offers user-controllable composition and compliance, to which a variety of growth factors or matricellular proteins may be added. 9,10 The elastic moduli of hydrogels can be tailored to match the cell type to achieve optimal regeneration of a new tissue. 11,12 Design criteria for ECM mimetics.…”
Section: Introductionmentioning
confidence: 99%